Transcriptional regulation of intermediate progenitor cell generation during hippocampal development - Harris, L.; Zalucki, O.; Gobius, I.; McDonald, H.; Osinki, J.; Harvey, T.; Essebier, A.; Vidovic, D.; Gladwyn-Ng, I.; Burne, T.; Heng, Julian; Richards, L.; et al. (Company of Biologists LTD, 2016)
© 2016. Published by The Company of Biologists Ltd. During forebrain development, radial glia generate neurons through the production of intermediate progenitor cells (IPCs). The production of IPCs is a central tenet underlying the generation of the appropriate number of cortical neurons, but the transcriptional logic underpinning this process remains poorly defined. Here, we examined IPC production using mice lacking the transcription factor nuclear factor I/X (Nfix). We show that Nfix deficiency delays IPC production and prolongs the neurogenic window, resulting in an increased number of neurons in the postnatal forebrain. Loss of additional Nfi alleles (Nfib) resulted in a severe delay in IPC generation while, conversely, overexpression of NFIX led to precocious IPC generation. Mechanistically, analyses of microarray and ChIP-seq datasets, coupled with the investigation of spindle orientation during radial glial cell division, revealed that NFIX promotes the generation of IPCs via the transcriptional upregulation of inscuteable (Insc). These data thereby provide novel insights into the mechanisms controlling the timely transition of radial glia into IPCs during forebrain development.